Darut Taubah Pesantren and Commercial Sex Workers Saritem in Bandung - Juju Saepudin (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
The establishing a pesantren in a prostitution area is a very interesting topic to bestudied. This is because the challenge would be different from building a pesantren inother community situations. This article based on the research on the roles of DarutTaubah pesantren in teaching of moral values to commercial sex workers at Saritemprostitution area. This is a qualitative case study research using a phenomenology approach. Data was gathered using observation, in-depth interview, and documentary research. Data was analyzed utilizing inductive approach. Finding of this study showsthat the establishment of Darut Taubah pesantren was motivated by cultural andstructural factors. Moreover, teaching of moral values was conducted through reorganizing structural and instrumental elements using many ways namely; persuasive method and prioritizing the roles of pesantren, teaching moral values and developing the social roles. After the existence of Darut Taubah pesantren in Saritem area, the prostitutionactivities decrease significantly either in terms of quantity or intensity.